Pengaruh Tingkat Stres terhadap Kejadian Emotional Eating pada Mahasiswi Kedokteran Tingkat 1 Unisba - Siska Firdayanti; Nuzirwan Acang; Sadiah Achmad (UNISBA Press, 2023)
Abstract. Stress is a person's reaction both physically and emotionally that can occur due to negative thoughts or feelings about oneself. Negative emotions can cause a response in the form of emotional eating. Emotional eating is a form of coping strategy to deal with stress and anxiety. Based on this phenomenon, the problems in this study are formulated as follows: (1) What is the description of the stress level of Unisba level one medical students? (2) What is the description of the emotional eating behavior of Unisba first year medical faculty students? (3) Is there a relationship between stress and emotional eating behavior in first year students at Unisba? Researchers used the method of observational analysis with a cross sectional approach. The population selected in this study were first-level medical students at Unisba, totaling 172 female students. With the sampling technique, namely simple random sampling, the number of research samples was obtained as many as 90 female students. Data collection techniques used in this study were questionnaires. The data collection technique used in this study was a questionnaire. The data analysis technique was carried out using univariate and bivariate methods with the Chi-Square test. The results of this study are: There is no relationship between stress and emotional eating in level 1 female students at Unisba. Abstrak. Stres adalah reaksi seseorang baik secara fisik maupun emosional yang dapat terjadi karena pikiran atau perasaan negatif tentang diri sendiri. Emosi negatif dapat menimbulkan respon berupa emotional eating. Emotional eating merupakan bentuk coping strategy untuk mengatasi stres dan kecemasan. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana gambaran tingkat stres mahasiswi fakultas kedokteran tingkat satu Unisba? (2) Bagaimana gambaran perilaku emotional eating mahasiswi fakultas kedokteran tingkat satu Unisba? (3) Apakah terdapat hubungan antara stres dan perilaku emotional eating pada mahasiswi tingkat satu Unisba?. Peneliti menggunakan metode analisis observasional dengan pendekatan cross sectional. Populasi yang dipilih dalam penelitian ini adalah mahasiswi fakultas kedokteran tingkat satu Unisba yang berjumlah 172 mahasiswi. Dengan teknik pengambilan sample yaitu simple random sampling diperoleh jumlah sampel penelitian sebanyak 90 mahasiswi. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner. Adapun teknik analisis data dilakukan dengan cara univariat dan bivariat dengan uji Chi-Square. Hasil dari penelitian ini adalah: Tidak terdapat hubungan antara stres dengan emotional eating pada mahasiswi tingkat 1 Unisba.